KEBIJAKAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN PEREMPUAN DI KABUPATEN DEMAK - Sri Kusriyah Kusriyah (UNISSULA, 2017)
The general explanation of Law No. 23 of 2014 on Regional Government explains that thegranting of the broadest autonomy to the regions is directed to accelerate the realization of thewelfare of the community through the improvement of services, empowerment, and communityparticipation. This research is related to community empowerment, especially local government policyin women empowerment. The method used in normative juridical research is by reviewing variouslaws related to women empowerment, especially the policy of local government of Demak regency,and to examine the programs conducted by the government Regions through the Office of Women’sEmpowerment. To analyze the research results used qualitative analysis by giving interpretationof local government policy related to empowering woman to answer problem in this research. Theresults showed that the policy of Demak Regency Government in the empowerment of women is:a) Empowerment of women entered in one of the Head of District Mission in 2011-2016, BupatiRegulation No. 07 of 2012 on General Guidelines Implementation of Gender Mainstreaming in DemakDistrict, 401/0057/2016 on Gender Responsive Planning and Budgeting SKPD.b) Work programsimplemented by KP2PA include: 1) improvement of women’s quality of life and child protection, 2)institutional strengthening of gender mainstreaming, 3) harmony of policies to improve the qualityof children and women,4) enhancement of participation and gender equality in development